Planning method of droplet fusion scheduling based on mixed-integer programming - Xiong, JiaCong; Chen, JianKui; Wang, YiXin; Yin, ZhouPing; Li, YiQun (Science China. Technological sciences, 2024)
The emergence of new display devices, such as organic light-emitting diodes, has brought about numerous advantages, including high material utilization, low cost, and high adaptability. These devices are manufactured using inkjet printing and possess the potential to become a key technology for display transformations. However, a challenge in achieving this is the display effect that reveals uneven brightness and darkness, which can be avoided by controlling the volume of ink solution in a pixel to within 5%. Currently, the volume difference among the nozzles of commercial printheads does not meet the requirements for volume uniformity, thus challenging the printing process. Therefore, designing a suitable printing method that allows for the fusion of different volumes of ink droplets, ultimately reducing the error of the post fusion process, is necessary. In this study, we propose a print display droplet fusion scheduling method comprising two main steps. First, we use a dichotomous trust domain algorithm to obtain a feasible range of printhead docking point spacings for different nozzle and pixel panel resolutions. Second, we model the printing process as a droplet fusion scheduling model based on mixed integer programming, with the optimization objective of achieving intra pixel volume uniformity via ensuring the volume uniformity of ink droplets within all pixels. We verified this method through numerical simulations and printing experiments using 394 pixels per inch (ppi) pixel panels and successfully reduced the volume uniformity error among pixels to within 5%.